2010
DOI: 10.1080/15504281003705238
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence, Elder Abuse, and Sexuality of Transgender Adults, Age 50+: Results of Three Surveys

Abstract: Relatively little is known about the lives of transgender people once they are through their gender transition. Even less is known about transgender elders, either those who transitioned many decades ago and now have grown older or those who are transitioning in mid-or later-life. This article reports on the findings of three online surveys of transgender adults age 50 years and older on three topics: sexual violence, elder abuse, and sexuality. Sexual violence and elder abuse had been experienced by a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 7 publications
2
71
0
Order By: Relevance
“…The most common types of abuse were emotional, verbal, physical, and neglect. In a study of transgender older adults, two-thirds reported having received unwanted sexual touch, with 55% reporting such abuse was related to their perceived gender expression or presentation [74]. …”
Section: Resultsmentioning
confidence: 99%
“…The most common types of abuse were emotional, verbal, physical, and neglect. In a study of transgender older adults, two-thirds reported having received unwanted sexual touch, with 55% reporting such abuse was related to their perceived gender expression or presentation [74]. …”
Section: Resultsmentioning
confidence: 99%
“…As documented by recent studies, persons who identify as "gender variant" (Lombardi, 2009) are frequently subjected to discrimination (Sánchez & Vilain, 2009), sexual violence and elder abuse (Cook-Daniels, 1995;Cook-Daniels & Munson, 2008), and hate crimes that can be classified as a form of genocide (Kidd & Witten, 2008a). If in addition to identifying as transgender or transsexual, one is also gay, lesbian, or bisexual, the risk of being the object of hate crimes may increase.…”
Section: T M Wittenmentioning
confidence: 99%
“…[29][30][31] The global, transgender-identified population has routinely faced extreme discrimination on the part of health-care workers in all areas of health-care delivery. 3,29,32 Persons who identify as ''gender variant'' 3,33 are frequently subjected to discrimination, sexual violence and elder abuse, 34 and hate crimes. 27,28 Moreover, given that many of the current elders of the trans-population grew up in this adverse biomedical and psycho-socio-economic environment, many are fearful and/or unwilling to interact with health-care providers.…”
Section: Literature Search Findingsmentioning
confidence: 99%